2014
DOI: 10.1186/s12884-014-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation, dietary folate intake during pregnancy and risk for spontaneous preterm delivery: a prospective observational cohort study

Abstract: BackgroundHealth authorities in numerous countries recommend periconceptional folic acid supplementation to prevent neural tube defects. The objective of this study was to examine the association of dietary folate intake and folic acid supplementation during different periods of pregnancy with the risk of spontaneous preterm delivery (PTD).MethodsThe Norwegian Mother and Child Cohort Study is a population-based prospective cohort study. A total of 66,014 women with singleton pregnancies resulting in live birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…This result differed from the result of a systematic review and meta-analysis including eight randomized controlled studies, which indicated a 2% increase in infant birth weight for every two-fold increase in folate intake (94). No association between intake of total folate and preterm delivery was found in MoBa (33), which is in line with the mentioned systematic review and meta-analysis (94).…”
Section: Possible Explanations For Findings and Comparison With Othercontrasting
confidence: 59%
See 1 more Smart Citation
“…This result differed from the result of a systematic review and meta-analysis including eight randomized controlled studies, which indicated a 2% increase in infant birth weight for every two-fold increase in folate intake (94). No association between intake of total folate and preterm delivery was found in MoBa (33), which is in line with the mentioned systematic review and meta-analysis (94).…”
Section: Possible Explanations For Findings and Comparison With Othercontrasting
confidence: 59%
“…[12][13][14], some testing hypotheses related to pregnancy outcomes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), some testing hypotheses related to later health outcomes in mothers and children (e.g. [34][35][36][37], and some in which dietary factors were included as predictors or confounding variables (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A possible risk reduction of CHD by intake of folic acid or multivitamin supplements is likely determined by the extent of dietary vitamin insufficiency in the population. The dietary folate intake reported in pregnant Norwegian women, around 300 μg per day, 21 could be sufficient for fetal cardiac development, as opposed to certain Chinese provinces with a high prevalence of folate deficiency, where the risk of CHD has been significantly reduced when mothers had used periconceptional folic acid supplements. 22 Alternatively, the dose of folic acid supplement in the present study, 400 μg per day, is too small to prevent cardiac malformations, although plasma folate has been found to be significantly higher in women reporting folic acid supplement use.…”
Section: Commentmentioning
confidence: 93%
“…Observational studies showed that folic acid supplementation during conception was associated with the increased risk of wheezing in children through 18 months of age (dose was not reported) [60] and the increased risk of infant asthma (>72,000 μg∙day) [61]. Evidence from observational studies showed that folic acid supplementation was associated with the increased risk of infant clefts (dose was not reported) [62] and spontaneous preterm delivery (mean dose (interquartile range): 313 (167–558) μg/day) [63]. Valera-Gran et al found that high folic acid supplementation for mothers during conception (>5000 μg/day) had a detrimental effect on the psychomotor development of children [64].…”
Section: B-vitamins One-carbon Metabolism and Ntdsmentioning
confidence: 99%